Treatment Response in Pediatric Pulmonary Tuberculosis—A Prospective Longitudinal Study. Issue 7 (24th April 2022) - Copelyn, Julie; Eley, Brian; Cox, Helen; Workman, Lesley; Dheda, Keertan; Nicol, Mark P; Zar, Heather J
Abstract: Background: Data are limited on the resolution of symptoms and signs in children treated for pulmonary tuberculosis (PTB) and whether this resolution differs from children with other lower respiratory tract infections (LRTIs). Methods: A prospective study of children ≤ 15 years presenting with features suggestive of PTB was performed. Clinical, microbiological, and radiological investigations were done at enrollment. Symptoms and clinical features were measured 1, 3, and 6 months after enrollment. Participants were categorized into 3 groups based on National Institutes of Health consensus definitions: confirmed PTB, unconfirmed PTB, and unlikely PTB (children with other LRTIs). Univariable and multivariable logistic regression modeling was used to investigate predictors of persistence of symptoms or signs. Results: Among 2019 participants, there were 427 (21%) confirmed, 810 (40%) unconfirmed, and 782 (39%) with unlikely PTB. Of 1693/2008 (84%) with cough and 1157/1997 (58%) with loss of appetite at baseline, persistence at 3 months was reported in 24/1222 (2%) and 23/886 (3%), respectively. Of 934/1884 (50%) with tachypnoea and 947/1999 (47%) with abnormal auscultatory findings at baseline, persistence at 3 months occurred in 410/723 (57%) and 216/778 (28%), respectively. HIV infection and abnormal baseline chest radiography were associated with persistence of symptoms or signs at month 3 (adjusted odds ration [aOR] 1.6; 95% confidence interval [CI]: [1.1, 2.3] and aOR 2.3; 95% CI: [1.5, 3.3], respectively]. The resolution of symptoms and signs was similar across categories. Conclusions: Symptoms resolved rapidly in most children with PTB, but signs resolved more slowly. The pattern and resolution of symptoms or signs did not distinguish children with PTB from those with other LRTIs. Abstract : In children treated for pulmonary tuberculosis, symptoms resolved rapidly in most, but signs resolved more slowly. The pattern and timing of resolution of symptoms and signs cannot distinguish children with pulmonary tuberculosis from those with other lower respiratory tract infections.